Novel ASON routing implementation - LI Jian; YANG Ai-ping; GU Wan-yi; ZHANG Jie (Tongxin xuebao)
An OSPF-based ASON routing implementation was proposed.In the implementation a wavelength LSA and network node LSA were extended to distribute wavelength and topology information.The topology was discovered automatically and routing messages were delivered reliably.In addition,the RWA interface was designed to introduce RWA algorithms easily.The simulation results show that the routing protocol implementation could converge rapidly and could be extended easily at low protocol overhead.The routing information flooding trigger strategies and the feasibility of flooding wavelength information throughout the network are also analyzed.